2001
DOI: 10.1097/00006123-200108000-00022
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3 and αvβ5 Integrin Expression in Glioma Periphery

Abstract: Our data support the role of integrins alpha(v)beta3 and alpha(v)beta5 in glioma-associated angiogenesis. In addition, they suggest a role for integrin alpha(v)beta3 in neoangiogenesis and cell migration in high-grade glioma periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(159 citation statements)
references
References 43 publications
5
151
1
2
Order By: Relevance
“…Otherwise, the radioactivities found in all the other dissected organs were in the same range for both the LNC throughout the studied time scale. There were minor differences in the circulation time of the LNC tested, however the differences were not statistically significant: 46.7±5.3% and 39.8±5.6% at 1 h, 35.0±4.0% and 30.7±3.5% at 3h, and 3.2±0.5% and 3.3±0.1% at 24 for LNC-cRGD and LNC-cRAD, respectively. Radioactivity levels observed in tumours were the following: ID/g values 3.6±1.1%, 3.5±0.4% and 4.0±1.3% (LNC-cRGD) and 1.8±0.4%, 2.1±0.8% and 3.4±0.6% (LNC-cRAD) at 1, 3 and 24 h, respectively.…”
Section: In Vivo Biodistributionmentioning
confidence: 79%
See 1 more Smart Citation
“…Otherwise, the radioactivities found in all the other dissected organs were in the same range for both the LNC throughout the studied time scale. There were minor differences in the circulation time of the LNC tested, however the differences were not statistically significant: 46.7±5.3% and 39.8±5.6% at 1 h, 35.0±4.0% and 30.7±3.5% at 3h, and 3.2±0.5% and 3.3±0.1% at 24 for LNC-cRGD and LNC-cRAD, respectively. Radioactivity levels observed in tumours were the following: ID/g values 3.6±1.1%, 3.5±0.4% and 4.0±1.3% (LNC-cRGD) and 1.8±0.4%, 2.1±0.8% and 3.4±0.6% (LNC-cRAD) at 1, 3 and 24 h, respectively.…”
Section: In Vivo Biodistributionmentioning
confidence: 79%
“…Glioblastomas are aggressive, highly vascularized brain tumours that display poor patient survival and prognosis with current therapies. These tumours and the associated newly formed vasculature express α v β 3 integrin [35].…”
Section: Introductionmentioning
confidence: 99%
“…Integrin α v β 3 is expressed on the most aggressive tumor cells in many cancers including high-grade glioma [21], and its expression correlates with metastasis by recruiting c-Src to integrin β 3 [22]. Recent study has revealed that integrin β 3 is necessary and sufficient to account for stemness and drug resistance by activating Ras/RalB/TBK1/NF-κB pathway [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin α v β 3 is a receptor for the extracellular matrix proteins with exposed arginine-glycine-aspartic (RGD) tripeptide sequence [6][7][8][9][10]. Integrin α v β 3 is normally expressed at low levels on epithelial cells and mature endothelial cells; but it is highly expressed on the activated endothelial cells in neovasculature of tumors, including osteosarcomas, glioblastomas, melanomas, lung carcinomas, and breast cancer [5,[11][12][13][14][15][16][17][18]. It has demonstrated that integrin α v β 3 is overexpressed on both endothelial and tumor cells in human breast cancer xenografts [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has demonstrated that integrin α v β 3 is overexpressed on both endothelial and tumor cells in human breast cancer xenografts [19]. It was also reported that the integrin α v β 3 expression correlates well with tumor progression and invasiveness of melanoma, glioma, ovarian and breast cancers [8][9][10][11][12][13][14][15][16][17][18]. The highly restricted expression of integrin α v β 3 during tumor growth, invasion and metastasis present an interesting molecular target for early detection of rapidly growing and metastatic tumors [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%